PENGARUH RELATIONAL BENEFITS TERHADAP RELATIONAL OUTCOMES BEHAVIORAL (WOM, TRUST&COMMITMENT) MELALUI SATISFACTION (SURVEI PADA NASABAH PT. BANK NEGARA INDONESIA WILAYAH JAKARTA) - Hielvita Ludiya (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2010)
The background of this research was to prove the relationship marketing as approaches for attract, maintain and enhance customer relationship and to build competitive advantages strategy. To pass relationship marketing mainly concentrated on analysis of benefits (relational benefits). PT. Bank NegaraIndonesia as financial service provider makes relationship with their partner, in there many problem in those relationship.The objective of this research is know the influence of perceived relational benefits on relational outcomes behavioral (word of mouth, trust&commitment) to pass satisfaction during in PT. Bank Negara Indonesiatoward the reality act of the PT. Bank Negara Indonesia service. In the highly competitive service industries such as bank, it is very essential to encourage the patterns of continuous the repurchase and to retain customers. This may be achieved through the quality of the relationship that was establishedbetween the service provider and the customer’s.The design of this research applies a survey toward unit of analysis on PT.Bank Negara Indonesia to interview the customers for testing hypothesis. Mean while the required data consist of eight variables;confidence benefits, social benefits, convenience benefits and employee’s social regard attribute as independent variables, satisfaction as intervening variable and word of mouth, trust and commitmentas dependent variable. The design of this research applies the Likert-scale for the 5 point measurement which means strongly agree and 1 point is for strongly disagree. The aggregate numbers of customer being respondent of the study are 170.The result of this research conclude that two variable of relational benefits which is confidence benefits and employee’s social regard effecting to satisfaction. Meanwhile two variable, social benefits and convenience benefits didn’t effecting to satisfaction. And then satisfaction effecting to word of mouth,trust and commitment.Keywords : Service industries, Customer satisfaction, Individual perception, Customer relations